Clean dyeing of acrylic fabric by sustainable red bacterial pigment based on nano-suspension system. (25th January 2021) - Ren, Yanfei; Fu, Ranran; Fang, Kuanjun; Xie, Ruyi; Hao, Longyun; Chen, Weichao; Shi, Zhen
Abstract: Green preparation and application of microbial pigments are becoming a hotspot in the development and utilization of renewable resources. However, the application of microbial intracellular pigment in acrylic fabric dyeing is not environmentally friendly. In this research, different surfactant fermentation systems were employed to divert prodigiosins from the interior of thalli to the exterior during the liquid fermentation process. The results indicated that the extracting effect of nonionic surfactants was better than that of anionic surfactants. The maximum transfer ratio was obtained to be 94.3% when Tween 80 concentration was 18 g/L, which realized efficient clean extraction of prodigiosins without using organic solvent. The prepared prodigiosins suspension with the largest concentration of 226.0 mg/L was utilized as natural dyestuff for acrylic fabric dyeing, and the cationic dyeing technology based on nano-suspension system was developed. This research provided an original and green method for prodigiosins to simultaneously endow acrylic fabric with deep color ( K/S value 13.59) and antibacterial functionality (81.8% against S. aureus ), which has potential generalization for other microbial pigments. Graphical abstract: Image 1 Highlights: Efficient green transfer of intracellular prodigiosins to thalli exterior is realized. Cationic dyeing for acrylic fabric based on nano-suspension system was developed. This dyeing technique has potential generalization for other microbial pigments.